Hydrogen Release and Ignition in a Semi-Confined Area of a Fuel-Cell Truck Following Collision - Runefors, Marcus ; 0000-0001-5534-2217; Wilkens Flecknoe-Brown, Konrad ; 0000-0003-0435-5573; Camacho, Javier; Boman, Stig; Lundgren, Staffan (Hydrogen Safety, 2025)
With the projected increase in the number of hydrogen-fueled trucks, it can be expected that it will become more common for such vehicles to be involved in road collisions. Even if hydrogen vehicles are designed with a quick-closing valve on tanks in accordance with UN/ECE R134, a small volume of hydrogen will be contained downstream of this valve and in the fuel-cell recirculation system and thereby potentially be released in case of a crash. The amount of hydrogen in the pipework is only a few grams, but to verify that this would not pose a hazard, Volvo Trucks AB took the initiative for experiments in a realistic setting. The experiment was performed on an actual truck with a mockup of a fuel cell installed in the planned position. Releases between 3 and 14 g of hydrogen were tested with a very short release duration (less than 200 ms) based on crash simulations performed by Volvo. In total, 42 experiments were conducted: 25 without ignition to assess dispersion and 17 with ignition to assess overpressure and flame speed. The maximum average hydrogen concentration was approximately 16%, and the highest overpressure was in the order of 10 kPa. The conclusion was that the hypothesis (that the scenario would not generate hazardous overpressures due to the relative openness of the setup and low level of obstruction) was corroborated even when the released mass of hydrogen was significantly higher than the mass expected given the preliminary design by Volvo.
Keywords: FCEV; Trucks; Semi-open; Partially closed; Deflagration